Observational studies of supernovae and intermediate luminosity optical transients - Harmanen, Jussi (fi=Turun yliopisto|en=University of Turku|, 2020)
Thanks to modern all-sky surveys, thousands of astronomical transient events are discovered annually. Although many of these, such as regular supernovae (SNe), are fairly well understood, new rarer classes of transients have been discovered since the late 20th century. These include SNe interacting with dense circumstellar matter (CSM) and intermediate luminosity optical transients (ILOTs a.k.a. gap transients). Because of the limited number of facilities available, only a small fraction of all transients are spectroscopically classified. As a part of international collaborations, I have participated in the acquisition and processing of data for classification and follow-up of a variety of transient events. The main telescopes used were the Nordic Optical Telescope and the European Southern Observatory’sNewTechnology Telescope. Thewavelength regions observed span from the optical to the near-infrared. A total of 111 spectroscopic classifications and five selected follow-up papers that I have contributed to are discussed in this work. Two of the events, SNe 2015bh and 2016bdu are possibly produced by SNe interacting with CSM although other interpretations cannot be completely ruled out. The other three objects are ILOTs. SNhunt248 was likely produced either by an outburst from a yellow hypergiant star (SN impostor) or a binary merger (luminous red nova, LRN). The LRN M101OT2015-1was probably produced by a merger. A sub-energetic SN explosion in a dusty environment is favoured as the origin for the intermediate luminosity red transient (ILRT) AT 2017be. Even though ILOTs share many common observable similarities, such as their early spectral features and maximum luminosities, there are distinguishable characteristics to each subclass. SN impostors exhibit strong variability prior to their outbursts. The progenitors of ILRTs are low mass stars (compared to other SN progenitors, that is) surrounded by dusty CSM. LRNe are produced by binary merger and they tend to develop molecular spectral lines during the later stages of their evolution. In the case of so-called SN 2009ip -like transients (such as SNe 2015bh and 2016bdu), more data are required to fully understand these events. Although their photometric and spectral evolution is conspicuously similar, it is still not clear whether or not they are produced by a terminal SN explosion or, for instance, some erratic progenitor activity.

discovered annually. Although many of these, such as regular supernovae (SNe), are fairly well understood, new rarer classes of transients have been discovered since the late 20th century. These include SNe interacting with dense circumstellar matter (CSM) and intermediate luminosity optical transients (ILOTs a.k.a. gap transients). Because of the limited number of facilities available, only a small fraction of all transients are spectroscopically classified. As a part of international collaborations, I have participated in the acquisition and processing of data for classification and follow-up of a variety of transient events. The main telescopes used were the Nordic Optical Telescope and the European Southern Observatory’sNewTechnology Telescope. Thewavelength regions observed span from the optical to the near-infrared. A total of 111 spectroscopic classifications and five selected follow-up papers that I have contributed to are discussed in this work. Two of the events, SNe 2015bh and 2016bdu are possibly produced by SNe interacting with CSM although other interpretations cannot be completely ruled out. The other three objects are ILOTs. SNhunt248 was likely produced either by an outburst from a yellow hypergiant star (SN impostor) or a binary merger (luminous red nova, LRN). The LRN M101OT2015-1was probably produced by a merger. A sub-energetic SN explosion in a dusty environment is favoured as the origin for the intermediate luminosity red transient (ILRT) AT 2017be. Even though ILOTs share many common observable similarities, such as their early spectral features and maximum luminosities, there are distinguishable characteristics to each subclass. SN impostors exhibit strong variability prior to their outbursts. The progenitors of ILRTs are low mass stars (compared to other SN progenitors, that is) surrounded by dusty CSM. LRNe are produced by binary merger and they tend to develop molecular spectral lines during the later stages of their evolution. In the case of so-called SN 2009ip -like transients (such as SNe 2015bh and 2016bdu), more data are required to fully understand these events. Although their photometric and spectral evolution is conspicuously similar, it is still not clear whether or not they are produced by a terminal SN explosion or, for instance, some erratic progenitor activity.   Jatkuvasti taivasta kartoittavien havainto-ohjelmien ansiosta tuhansia lyhytikäisiä tähtitieteellisiä kohteita löydetään vuosittain. Tavallisimmat näistä kohteista – kuten supernovat – ovat varsin hyvin ymmärrettyjä. Harvinaisemmille kohteille tämä ei päde. Harvinaisiksi lasketaan muun muassa viime vuosituhannen loppupuolelta alkaen löydetyt uudet kohteet, joihin kuuluvat esimerkiksi tiheän tähteä ympäröivän aineen kanssa vuorovaikuttavat supernovat ja keskikirkkaat lyhytikäiset optiset kohteet (ILOT-kohteet). Havaintolaitteiden määrän rajallisuudesta johtuen uusista kohteista luokitellaan kuitenkin vain pieni murtoosa. Olen ollut mukana suurissa kansainvälisissä hankkeissa havaitsemassa ja käsittelemässä aineistoa monelle eri havaintokohteelle. Keskeisimmät käytössä olleet kaukoputket ovat Nordic Optical Telescope ja Euroopan eteläisen obsevatorion New Technology Telescope. Havainnot painottuivat näkyvän valon ja lähi-infrapunan alueille. Tässä työssä esitellään 111 kohteen spektroskoopiset luokitukset ja viisi valittua artikkelia, joihin olen kerännyt ja käsitellyt havaintoaineistoa. Kaksi kohteista, SN 2015bh ja SN2016bdu, ovat todennäköisesti seurausta tähteä ympäröivän aineen kanssa vuorovaikuttavasta supernovasta, joskaan muita tulkintoja ei voi täysin sulkea pois. Kohteen SNhunt248 kirkastumiselle on esitetty kaksi mahdollista tulkintaa: keltaisen ylijättiläistähden purkaus tai kaksoistähtijärjestelmän yhteensulautuminen. Kohteelle M101 OT2015-1 on myös esitetty jälkimmäistä tulkintaa. Pölyisessä ympäristössä räjähtänyt matalaenergeettinen supernova on puolestaan todennäköisin selitys kohteelle AT 2017be. Vaikkakin ILOT-kohteilla on yhteneväisiä havaittuja piirteitä, kuten spektrin yksityiskohtien kehitys ja kirkkauden maksimi, on jokaisella kohteella myös omat tunnusomaiset piirteensä. Esimerkiksi suuren tähden massiivista purkausta edeltää usein epästabiilisuus vuosien aikaskaalalla. Niin kutsutuille SN 2009ip -tyyppisille kohteille – joita myös kohteet SN 2015bh ja SN2016bdu edustavat – lisähavainnot ovat tarpeen. Vaikkakin havaitut ominaisuudet ovat suurilta osin samat, ei vielä tiedetä, että ovatko nämä kohteet seurausta supernovaräjähdyksestä vai esimerkiksi tähden epästabiilisuudesta, joka tuottaa supernovaa muistuttavia havaittavia piirteitä.